A novel method for distinguishing different algal blooms in the East China Sea via geostationary ocean color satellite observations - Zhao, Min; Li, Hao; Zhang, Xuan; Ding, Xiaosong; Gong, Fang (Frontiers in Marine Science, 2025)
IntroductionDinoflagellate and diatom blooms are the most frequent marine ecological disasters in the Yangtze River estuary (YRE) and adjacent areas of the East China Sea (ECS). Distinguishing between these bloom types is essential for accurate monitoring and effective mitigation.MethodsTo investigate the physiological differences between bloom types, algal culture experiments were conducted to quantify variations in fluorescence quantum yield (φ) between dinoflagellates and diatoms during the growth phase. Using insights from the experiments, an identification and classification method for harmful algal blooms (HABs) was developed based on Geostationary Ocean Color Imager-II (GOCI-II) data. The method incorporates the difference in remote sensing reflectance (Rrs) between the fluorescence peak and baseline bands and establishes a φ-based classification threshold.ResultsValidation of GOCI-II Level-2 products showed that fluorescence-band Rrs products have high accuracy and strong correlation with in situ measurements. A threshold of φ = 0.014 was proposed to distinguish dinoflagellate from diatom blooms. The derived methods were successfully applied to GOCI-II imagery, enabling precise detection and classification of HABs in ECS waters.DiscussionThe proposed approach demonstrated strong capability for monitoring the spatial distribution and evolution of HABs. It provides a reliable technique for distinguishing bloom types using geostationary satellite data, offering valuable support for marine environmental management and mitigation efforts.